The Transfer of Land Rights Uses the Selling Power of Official Certifier of Title Deeds (Case of Supreme Court Decision Number 3017 K/PDT/2019) - Tara Ulina Ginting; Benny Djaja (Edunity Kajian Ilmu Sosial dan Pendidikan, 2023)
The act of the Certifer of Title Deeds transferring the right to the land owned by the seller using the Deed of Power of Attorney to sell, a legal problem arises when transferring land rights by using the selling power of attorney from the Certifer of Title Deeds based on Government Regulation Number 24 of 2016 on. Amendment to Government Regulation No. 37 of 1998 concerning Regulations for the Positions of Officials Making Land Deeds. (Case Study Supreme Court Decision No. 3017 K/PDT/2019 JO Decision of the Central Examination Committee Number08/B/MPPN/IX/2018) and the responsibility of the Certifier of Title Deeds who transfer land rights by using the power of attorney. (Case Study of Supreme Court Decision Number 3017 K/PDT/2019 JO Decision of the Central Examination Committee of Notaries Number 08/B/MPPN/IX/2018). This research uses normative juridical research. The research results obtained that the transfer of rights to land using power of attorney for sale, binding sale-purchase agreement, and disposal of object certificates of owner Bachelor of Law only have the power of underhand deed so that cancellation can be requested. Based on the Decision of the Central Examination Council of Notaries Number 08/B/MPPN/XI/2018 Notaries and Certifer of Title Deeds Muhammad Irsan, Bachelor of Law was imposed administrative sanctions that have been by statutory regulations and Supreme Court Decision No. 3017 K/PDT/2019 can be examined in more depth regarding the main points of the case and is subject to sanctions for unlawful acts as the legal basis for the lawsuit.